(untitled) (Sociologisk Forskning, 2023)
Crime and punishment are often described as emotionally-charged fields. The present article aims to concretise this account by addressing how different political actors make use of emotions in distinct ways in order to advance their criminal policy in Sweden. Drawing on sociological research on emotions, I illustrate how the Moderate Party and the Social Democratic Party both make use of worry and (dis)trust in their electoral campaigning. However, the article also shows that the two political parties differ in the ways they encourage the Swedish public to engage emotionally in criminal policy matters which may entail different political effects.